Mechanisms of accidental fall injuries and involved injury factors: a registry-based study - Unguryanu, Tatiana Nikolaevna (Inj Epidemiol, 2020)
BACKGROUND: Falls are the leading cause of injury-related morbidity and mortality worldwide, but fall injury circumstances differ by age. We studied the circumstances of accidental fall injuries by age in Shenkursk District, Northwest Russia, using the data from the population-based Shenkursk Injury Registry. METHODS: Data on accidental fall injuries (hereafter: fall injuries) occurring in January 2015–June 2018 were extracted from the Shenkursk Injury Registry (N = 1551) and categorized by age group (0–6, 7–17, 18–59, and 60+ years). The chi-square test and ANOVA were used to compare descriptive injury variables across age groups, and a two-step cluster analysis was performed to identify homogeneous groups of fall injuries by preceding circumstances. RESULTS: Half of recorded fall injuries in the 0–6 year age group occurred inside dwellings (49%). The largest cluster of falls (64%) mainly included climbing up or down on home furnishings. In the 7–17 year age group, public outdoor residential areas were the most common fall injury site (29%), and the largest cluster of falls (37%) involved physical exercise and sport or play equipment. Homestead lands or areas near a dwelling were the most typical fall injury sites in the age groups 18–59 and 60+ years (31 and 33%, respectively). Most frequently, fall injury circumstances in these groups involved slipping on ice-covered surfaces (32% in 18–59 years, 37% in 60+ years). CONCLUSION: The circumstances of fall injuries in the Shenkursk District varied across age groups. This knowledge can be used to guide age-specific preventive strategies in the study area and similar settings.